The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0102-09352009000200026
|View full text |Cite
|
Sign up to set email alerts
|

Composição física da carcaça e qualidade da carne de novilhos Charolês e Nelore que receberam diferentes proporções de concentrado na dieta

Abstract: RESUMOAvaliaram-se a composição física da carcaça e a qualidade da carne de 22 novilhos contemporâneos, com média de idade de 22 meses, das raças Charolês ou Nelore, terminados em confinamento, e que receberam diferentes proporções de concentrado na dieta. A fração volumosa da dieta foi composta pelas silagens de milho e sorgo em partes iguais. Os animais foram distribuídos em três tratamentos constituídos por 35, 50 ou 65% de concentrado na matéria seca. Não houve efeito (P>0,05) da porcentagem de concentrado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…According to Owens et al, (1993) the excess of nutrients can be converted into lipids, excreted or catabolized. Silveira et al (2009) did not find differences in the carcass composition of animals fed diets with different energy densities above the maintenance level, attributing the lack of differences to the slaughter weight, as it is highly correlated to the quantitative characteristics of the carcass.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…According to Owens et al, (1993) the excess of nutrients can be converted into lipids, excreted or catabolized. Silveira et al (2009) did not find differences in the carcass composition of animals fed diets with different energy densities above the maintenance level, attributing the lack of differences to the slaughter weight, as it is highly correlated to the quantitative characteristics of the carcass.…”
Section: Resultsmentioning
confidence: 77%
“…The lower tissue deposition in Nellore animals addressed the lower carcass gain in these animals (0.640) compared with the crossbred animals (0.860). Crossbred animals had greater gain probably due to the heterosis effect (Teixeira & Albuquerque, 2005). It can be inferred that Nellore cattle need more time at the feedlot to reach the slaughter weight and adequate finishing score due to their lower muscle growth rate (Bianchini, 2005) compared with the other genetic types evaluated in this trial.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Silveira et al (2009) found that increasing the concentrate content reduced liquid loss in Charolais young bulls, but not in Nellore young bulls. Menezes et al (2005) found that subcutaneous fat thickness was not changed in Charolais young bulls' carcass, but this characteristic showed quadratic variation with the advance of concentrate in the ration of Nellore young bulls.…”
Section: Introductionmentioning
confidence: 89%
“…However, data related to the use of grass silage in the ration of feedlot cattle are still limited, especially regarding the effect on carcass characteristics and beef meat. In general, studies have shown that increasing the proportion of traditional silages (maize and sorghum) in the diet may harm important carcass characteristics (thawing loss, physiological maturity and pistol cut proportion) and meat characteristics (tenderness, texture and color) (SILVEIRA et al, 2009;MISSIO et al, 2010). However, some studies (CRUZ et al, 2014(CRUZ et al, , 2015a(CRUZ et al, , 2015b have shown that diets with high concentrate levels did not affect the performance and carcass characteristics of feedlot beef cattle, wherein the higher grass silage content of diets (350 vs. 190 g/kg) reduced feeding cost.…”
Section: Introductionmentioning
confidence: 99%